(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The objectives of the activity on ’Effective Digital Marketing Strategy Training for Online Marketing of Products Guided by Aisyiyah Leaders, North Purwokerto Branch, Banyumas Regency’, are: a) Provide counseling and training on creating digital media accounts tailored to the needs of the fostered residents, b) provide counseling and training on optimizing existing facilities on digital media accounts, c) providing counseling about the importance of adapting quickly in the online era, especially during the covid 19 pandemic. The training method is by providing material as the implementation of science and technology activities for the community which is carried out through online media (Zoom). meeting) by reason of being able to reach various regions of the participant’s domicile origin. The successful use of zoom meetings is a driving factor to improve technology capabilities for all implementing committees, partners and participants. Even so, there are weaknesses in the use of zoom meetings which are considered as obstacles or obstacles to activities. The main requirement for operating zoom meetings is to use communication tools that are able to access applications and signals (HP or Laptop and the like). Smooth signal access is highly dependent on the weather, the availability of access, the location of the participants, and the ability to use communication tools. The results of IBM’s activities include: a) this event becomes interesting to motivate partners and participants in trying to have a digital marketing account. b) Partners and participants have knowledge in seizing opportunities to increase business through online. c) With this activity, partners and participants try to adapt or adapt to participate in developing online businesses.